An algorithm for LES of premixed compressible flows using the Conditional Moment Closure model - Thornber, Ben; Bilger, R. W.; Masri, A. R.; Hawkes, E. R. (Elsevier, 2011)
A novel numerical method has been developed to couple a recent high order accurate fully compressible upwind method with the Conditional Moment Closure combustion model. The governing equations, turbulence modelling and numerical methods are presented in full. The new numerical method is validated against direct numerical simulation (DNS) data for a lean premixed methane slot burner. Although the modelling approaches are based on non-premixed flames and hence not expected to be valid for a wide range of premixed flames, the predicted flame is just 10% longer than that in the DNS and excellent agreement of mean mass fractions, conditional mass fractions and temperature is demonstrated. This new numerical method provides a very useful framework for future application of CMC to premixed as well as non-premixed combustion.
Keywords: Conditional Moment Closure; Large Eddy Simulation; Compressible; Combustion; Premixed; Turbulent combustion; Non-premixed